Eye movements in repeated multiple object tracking - Lukavský, Jiří (Journal of vision, 2013)
Contrary to other tasks (free viewing, recognition, visual search), participants often fail to recognize repetition of trials in multiple object tracking (MOT). This study examines the intra- and interindividual variability of eye movements in repeated MOT trials along with the adherence of eye movements to the previously described strategies. I collected eye movement data from 20 subjects during 64 MOT trials at slow speed (5°/s). Half of the trials were repeated four times, and the remaining trials were unique. I measured the variability of eye-movement patterns during repeated trials using normalized scanpath saliency extended to the temporal domain. People tended to make similar eye movements during repeated presentations (with no or vague feeling of repetition) and the interindividual similarity remained at the same level over time. Several strategies (centroid strategy and its variants) were compared with data and they accounted for 48.8% to 54.3% of eye-movement variability, which was less then variability explained by other peoples' eye movements (68.6%). The results show that the observed intra- and interindividual similarity of eye movements is only partly explained by the current models.
Keywords: Humans; Space Perception; spatial vision; Female; mladý dospělý; eye movements; lidé; Form Perception; Photic Stimulation; světelná stimulace; attention; multiple object tracking; Saccades; ženské pohlaví; vnímání tvaru; Male; active vision; sakadické oční pohyby; Young Adult; mužské pohlaví; vnímání prostoru